Findings of the unusual plasma bubble occurrences at dawn during the recovery phase of a moderate geomagnetic storm over the Brazilian sector. (1st September 2022) - Carmo, C.S.; Denardini, C.M.; Figueiredo, C.A.O.B.; Resende, L.C.A.; Moro, J.; Silva, R.P.; Nogueira, P.A.B.; Chen, S.S.; Picanço, G.A.S.; Neto, P.F. Barbosa
Abstract: In this work, we observe for the first time the unusual pre-sunrise Equatorial Plasma Bubbles (EPBs) during a moderate geomagnetic storm recovery phase caused by the High-Speed Solar Wind Stream (HSS) on February 17, 2015, over the Brazilian sector. Therefore, this study aims to explain the generation mechanism of this uncommon event, which started at 08:00 UT on February 18, 2015. We used Multiple Global Navigation Satellite Systems (Multi-GNSS, GPS, and GLONASS) data to produce two-dimensional maps of the Rate Of TEC index (ROTI) that show EPB features elongated in magnetic meridians. Also, Digisonde data from São Luís (2.53° S, 44.30° W, dip angle: 8.57°), Boa Vista (12.81° N, 60.67° W, dip angle: 33.71°), and Campo Grande (20.44° S, 54.64° W, dip angle: 25.98°), and magnetometer data at São Luís and Eusébio (3.89° S, 38.45° W, dip angle: 17.96°). Our analysis shows that the unusual pre-sunrise plasma bubbles lasted longer after sunrise, around 1 h. Finally, we showed that these EPBs are likely driven by a disturbance wind dynamo effect, which helps to understand the role of the external factors in EPBs development. Highlights: Atypical pre-sunrise EPBs are observed in a moderate geomagnetic storm for the first time in the Brazilian sector. The time duration of the atypical EPBs had lasted longer, around 1 h after sunrise between 09:00 UT and 10:00 UT. The zonal eastward electric field of the DDEF was the main agent to generate these atypical pre-sunrise EPBs.